A potential development of haze detection system using an open-path optical method - Nurulain, S.; M. S., Najib; Alsibai, Mohammad Hayyan; Mohd Rusllim, Mohamed; M. R., Salim; Hadi, Manap (Blue Eyes Intelligence Engineering & Sciences Publication, 2018)
This paper describes a potential development of haze measurement system by measuring visibility of a medium instead of measuring concentration of particulate matter in air. This measurement system is using an open path optical method to measure visibility of a few series of known-VLT thin film. VLT or visible light transmission rate plays an important role in order to determine the visibility of a medium and can be an alternative method to determine the haze index. Current instrument to measure haze is very big in size and cost too expensive relatively. Therefore an alternative method using a laser pointer as a light source and a spectrometer as a detector is introduced. The result shows that the measurement system is capable to measure a few series of known-VLT thin film within the visible light region (535-540 nm). It shows that this measurement system is capable to measure the visibility of haze and the response time is less than 1 s is reported.